Pengaruh pemberian pupuk bioboost terhadap pertumbuhan dan hasil tanaman zukini (Cucurbita pepo L.) varietas Zacky Z-6 - Thausa Ashriyani; Rini Sitawati; Sri Nur Widyastuti (University of Insan Cendekia Mandiri, 2022)
Zukini (Cucurbita pepo L.) belongs to the pumpkin tribe (Cucurbitaceae) including annual plants that live in the highlands. The need for zucchini in Indonesia is increasing along with the growing number of restaurants serving Japanese and Korean dishes. Information about the cultivation of zucchini in Indonesia is still limited, so that zucchini is rarely found among farmers. The purpose of the experiment was to get the right concentration of Bioboost fertilizer in order to give maximum zucchini yields. The experiment was conducted from February to April 2022 in Cihanjuang Rahayu Village, Parongpong, West Bandung Regency, West Java Province with an altitude of 1.243 m above sea level. The experiment menthod used complete randomized block design (CRBD) of five treatment and five replications. Each treatment consisted of 5 plants. so the total number was 125 plants. Treat the experiment A : 0 cc Bioboost/liter of water, B : 20 cc Bioboost/liter of water, C : 40 cc Bioboost/liter of water, D : 60 cc Bioboost/liter of water, E : 80 cc Bioboost/liter of water. The results showed that the concentration of Bioboost fertilizer was effective on the number of leaves, age of flower initiation, number of fruit/plant, fruit length/plant, fruit diameter/plant and fruit weight/plant. The application of Bioboost with a concentration of 60 cc/liter of water had the best effect on the growth and yield of the varieties Jacky Z-6 zucchini plant